Politik Dinasti Jokowi Dan Grand Corruption - Mozin, Sri Yulianty; Pakaya, Rahmatia; Halid, Intan Juleyka; Nurkamiden, Dwi Rahmatia; Umar, Suci Novia; Djafar, Nazwa Dita; Abdurahman, Sustri; Djaba, Aulia; Hiola, Fharel Putra (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
The phenomenon of political dynasty during President Joko Widodo's administration raises serious concerns about bureaucratic pathology and grand corruption. This study examines the political involvement of Jokowi’s family members-Gibran Rakabuming, Kaesang Pangarep, and Bobby Nasution—as indicators of power being utilized for familial benefit. A key issue analyzed is the Constitutional Court's controversial decision that enabled Gibran’s vice-presidential candidacy. Employing a postcolonial theoretical framework, the study explores how traditional values—such as the Javanese king myth—continue to shape public perception and power dynamics. The findings reveal that dynastic politics not only violate democratic ethics but also perpetuate structural corruption, undermine meritocracy, and pose a significant threat to the rule of law and democratic sustainability.